Analysis of Wood Pallet Quality Control with Six Sigma and FMEA Methods - Maghrufan Khakim; Said Salim Dahda (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This research was conducted at a logistics company engaged in warehousing and logistics services, or 3PL (third-party logistics service providers). Based on the results of the study, it is known that there are three types of product defects, the highest occurring during the last month, namely differences in pallet wood dimensions, cracks, and knots in pallet wood. From the FTA (Free Trade Agreement) diagram, it is known that the wood dimension product defect is a product defect that has the highest percentage of defects among other product defects, which is 62%. The processing results obtained an average DPMO value of 353.28 failures per one million, and the sigma level is around 3.33. Based on data analysis using Failure Mode and Effect Analysis, there are 3 product defects: dimensional differences, cracks, and knots on pallets. The main causes of product defects are checking goods from less careful suppliers, using damaged wooden pallets, and lacking lighting in the work area. Based on the analysis using SIX SIGMA and FMEA, quality improvement proposals for the company, namely conducting training and training so that employee knowledge and skills increase, selecting pallets that meet the standards, and adding lighting in the work area. Keywords: Defect, FTA, DPMO, Six Sigma, FMEA